Regularity estimates for the parabolic p(x, t)-Laplacian equation in Besov spaces. (December 2022) - Yao, Fengping
Abstract: The aim of this paper is to develop the local regularity estimates in Besov spaces for weak solutions to the following parabolic p ( x, t ) -Laplacian equation in divergence form u t − div | ∇ u | p ( x, t ) − 2 a ( x, t ) ∇ u = div F under some proper assumptions on the functions p ( x, t ), a ( x, t ) and F ( x, t ) . Moreover, we want to point out that our results improve the existed results for this kind of problems.